Population pharmacokinetic analysis of peficitinib in patients with rheumatoid arthritis. Issue 4 (1st December 2020) - Toyoshima, Junko; Shibata, Mai; Kaibara, Atsunori; Kaneko, Yuichiro; Izutsu, Hiroyuki; Nishimura, Tetsuya
Abstract : Aims: To analyse the population pharmacokinetics (PK) of peficitinib in patients with rheumatoid arthritis (RA) and assess the potential PK covariates to identify the requirement for dose adjustment in RA patients. Methods: The analysis incorporated 2464 observations from 98 healthy volunteers and 4919 observations from 989 RA patients. A population PK model for peficitinib in RA patients was constructed by a nonlinear mixed effect model using NONMEM with prior information from a healthy volunteer model. Results: A 2‐compartment model with sequential zero‐ and first‐order absorption and lag time was constructed for RA patients. Covariate exploration in the RA patient model revealed that estimated glomerular filtration rate (eGFR) and lymphocyte count had a significant effect on apparent total systemic clearance (CL), which was 91.7 L/h (2.3% relative standard error). Compared with the mean population CL, the model predicted mean changes in CL of 12.3 and −10.7% in patients with observed minimum and maximum lymphocyte count of 500 and 4600 10 6 /L, respectively, and mean changes in CL of −17.8 and 16.7% in patients with minimum and maximum eGFR of 36.4 and 188 mL/min/1.73m 2, respectively. The simulated population mean area under plasma concentration–time curve for 24 hours after dosing showed a 1.35‐fold increase in patients with severe renal impairment (eGFR 22.5 mL/min/1.73m 2 ) compared with patients with reference eGFR (91.5 mL/min/1.73m 2 ). Conclusion: The population PK model identified eGFR and lymphocyte count as covariates for CL. The magnitude of changes was not considered clinically relevant, indicating no requirement for dose adjustment.